No Easy Walk to Linguistic Freedom: A Critique of Language Planning During South Africa’s First Decade of Democracy - Gregory Hankoni Kamwendo (Nordic Journal of African Studies, 2006)
In 1994, South Africans of all races and political parties took part in the first democratic elections. The election and inauguration of Nelson Mandela as the first black president marked the beginning of a new era - an era of democracy. The new era has, among other things, witnessed reforms in language planning. The current paper is a critique of South Africa's language planning efforts during the first decade of democracy i.e. 1994-2004.